Efficacy and safety of Zuogui Pill in treating osteoporosis: Study protocol of a systematic review - Chen, Guoming (Medicine (Baltimore), 2019)
BACKGROUND: Osteoporosis (OP) is a common skeletal disorder worldwide, resulting in increased bone fragility and high risk of fractures. The Zuogui Pill (ZGP), a classic Chinese herbal formulation, has played a vital role in the clinical practice of OP in China for centuries. Increasing studies have been performed for clarifying its anti-osteoporotic mechanisms. However, this treatment still lacks a systematic review for its efficacy and safety in the treatment of OP. METHODS: Eight electronic databases will be searched from inception to November 2018 by 2 independent researchers, in order to collect qualified randomized controlled trials (RCTs) on the ZGP treatment for OP. The therapeutic effects according to bone mineral density (BMD) will be adopted as the primary outcomes. RevMan V.5.3 software will be used for the data synthesis and the Cochrane's risk of bias assessment tool will be used to assess the risk of bias. RESULTS: This review will conduct a high-quality synthesis on present evidence of ZGP for OP. CONCLUSION: The conclusion of the study will indicate whether ZGP is an effective treatment for OP by providing updated evidence. PROSPERO registration number: PROSPERO CRD 42018114366